Implementation of robot systems : an introduction to robotics, automation, and successful systems integration in manufacturing - Wilson, Mike, 1960- (Elsevier, BH, 2015)
"Based on the author's wide-ranging experience as a robot user, supplier and consultant, Implementation of Robot Systems will enable you to approach the use of robots in your plant or facility armed with the right knowledge base and awareness of critical factors to take into account. This book starts with the basics of typical applications and robot capabilities before covering all stages of successful robot integration. Potential problems and pitfalls are flagged and worked through so that you can learn from others' mistakes and plan proactively with possible issues in mind. Taking in content from the author's graduate level teaching of automation and robotics for engineering in business and his consultancy as part of a UK Government program to help companies advance their technologies and practices in the area, Implementation of Robot Systems blends technical information with critical financial and business considerations to help you stay ahead of the competition."--Resumé vydavatele
Keywords: automatizace; robotické systémy; průmyslové roboty; automatizované výrobní systémy; automation; robotic systems; industrial robots; automated manufacturing systems; příručky; elektronické knihy; handbooks and manuals; electronic books